Analysis of Factors Affecting the Income of Celery (Apium graveolens I) Producers in Kerinjing Agung Lawongan Village North Dempo Subdistrict Pagaralam City - Lisna Oktariani; Ilma Putri Rizki (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
In South Sumatra Province, celery plants are often found in highland sizes, such as the Pagar Alam area in Kerinjing Village, North Dempo District, which is one of the areas producing celery vegetables. In Kerinjing Village, celery plants have the potential to be developed. This research aims to decide the factors that impact the income of celery farmers and the amount of income generated from celery farming in Kerinjing Agung Lawongan Village, North Dempo District, Pagaralam City. This research was carried out from April 2023 to August 2023. It used a simple random method to take samples of farmers, while the Slovin method was used to decide the number of samples in this study, so the samples were 34 farmers from 150 populations. The variables employed in this study encompass farmer attributes such as age, educational attainment, agricultural experience, land size, and family size. The research used the multiple regression analysis method, utilizing SPSS and farming cost analysis for data processing. The research findings suggest that farming duration, production quantity, production expenses, and land size significantly affect the income variable. However, only the variables about the number of products and production costs exhibit a tangible impact. In contrast, the variables related to farming experience and land size do not demonstrate a substantial influence. The adjusted R-square in this study is 0.988, which means 98.8% of the independent variables can clarify the dependent variable. The average amount of celery production is 22,100 kg/Ha/MT, with the income of celery farmers being IDR. 97,475,400/Ha/MT.